A comparative study of mixed least-squares FEMs for the incompressible Navier-Stokes equations. (2018) - Schwarz, Alexander; Nickaeen, Masoud; Serdas, Serdar; Nisters, Carina; Ouazzi, Abderrahim; Schröder, Jörg; Turek, Stefan
In the present contribution, we compare (quantitatively) different mixed least-squares finite element methods (LSFEMs) with respect to computational costs and accuracy. Various first-order systems are derived based on the residual forms of the equilibrium equation and the continuity condition. The first formulation under consideration is a div-grad first-order system resulting in a three-field formulation with total stresses, velocities, and pressure (S-V-P) as unknowns. Here, the variables are approximated in H (div) × H 1 × L 2 on triangles and in H 1 × H 1 × L 2 on quadrilaterals. In addition to that a reduced stress-velocity (S-V) formulation is derived and investigated. S-V-P and S-V formulations are promising approaches when the stresses are of special interest, e.g., for non-Newtonian, multiphase or turbulent flows. The main focus of the work is drawn to performance and accuracy aspects on the one side for finite elements with different interpolation orders and on the other side on the usage of efficient solvers, for instance of Krylov-space or multigrid type.